Analisis Konsep Laba dalam Akuntansi Syariah: Perspektif Teoritis dan Praktis untuk Praktik Keuangan Berkelanjutan - Hasriady Hasriady; Septiani Wulan Purnamasari; Masyhuri Masyhuri (Journal of Economic and Business Advancement, 2025)
This study analyzes the concept of profit in Islamic accounting as a multidimensional construct that emphasizes not only financial performance but also values of fairness, ethics, and sustainability in line with the maqashid syariah. A qualitative approach based on literature review was used through a systematic search of academic literature, Islamic accounting standards, and empirical data from Islamic financial institutions to understand the relationship between the concepts of profit, governance, and sustainable finance practices. The results of the study show that strengthening internal controls, integrating Environmental, Social, and Governance (ESG) factors, and increasing sustainable financing play a significant role in shaping a broader and more beneficial definition of profit. Data on asset growth, profits, and sustainable financing portfolios in Islamic banking reinforce the finding that the application of spiritual values can go hand in hand with the achievement of positive economic performance. This study concludes that the concept of Islamic profit must be understood holistically as a reflection of halal activities, fair transactions, and real contributions to social and environmental welfare, thereby supporting sustainable financial practices.